Investigating the Viability of the Charity Based Model of Islamic Microfinance for Eradicating the Impact of Covid-19 on Social Wellbeing in Nigeria: A Discriptive Analysis - Maikabara, Abdullateef Abdulqadir; Aderemi, Abdulmajeed M.R.; Maulida, Sri (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2020)
The coronavirus known as (Covid-19) pandemic has posed a significant impact on social and economic sectors as many institutions and individuals face difficulties in meeting their needs. Over the years, Islamic microfinance has shown positively significant effects on socio-economic development. Recently, it is gaining strong momentum in the financial ground in Nigeria. The research aims to examine the perception of Islamic microfinance on social wellbeing as a relief measure to eradicate the impact of Covid-19. A total of 100 respondents were involved, and descriptive statistical analysis was used to measure the perception. The findings revealed that the charity-based model is viable for relieving the people' social wellbeing. The paper recommended proactive and constructive measures in implementing the model to generate fund for fighting against the outbreak and ensure social stability.